2019
DOI: 10.1186/s12864-019-6127-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute systemic inflammatory response to lipopolysaccharide stimulation in pigs divergently selected for residual feed intake

Abstract: Background It is unclear whether improving feed efficiency by selection for low residual feed intake (RFI) compromises pigs’ immunocompetence. Here, we aimed at investigating whether pig lines divergently selected for RFI had different inflammatory responses to lipopolysaccharide (LPS) exposure, regarding to clinical presentations and transcriptomic changes in peripheral blood cells. Results LPS injection induced acute systemic infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Another cause for concern is the balance between the benefits obtained from the study of the pathophysiology of sepsis and the well-being of the animals implicated in these experimental models [ 15 ]. However, LPS administration is considered an adequate model in pigs to study the pathophysiology of inflammation, immune system [ 13 , 16 , 17 ], and changes in biomarkers of oxidative status [ 18 ] associated with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Another cause for concern is the balance between the benefits obtained from the study of the pathophysiology of sepsis and the well-being of the animals implicated in these experimental models [ 15 ]. However, LPS administration is considered an adequate model in pigs to study the pathophysiology of inflammation, immune system [ 13 , 16 , 17 ], and changes in biomarkers of oxidative status [ 18 ] associated with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood is widely used in human medicine and veterinary fields as a relevant and easy sampling source of biological information, since it transports a large variety of molecules including DNA, coding and non-coding regulatory RNA, proteins and metabolites from all over the body. Their dynamics reflects homeostatic regulation [ 1 3 ], physiological changes [ 4 , 5 ] and variations in immune capacity [ 6 , 7 ]. Circulating molecules also provide valuable insights into complex phenotypes such as obesity and diabetes [ 8 , 9 ], health status [ 10 ], sensitivity to heat stress [ 11 ] and nutrient efficiency for productive outputs [ 3 , 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to find molecular biomarkers that accurately differentiate high and low FE animals and that can be further used for improving FE of growing animals in breeding programs or nutritional decision tools. So far, various studies have revealed differences in the whole blood transcriptome between low RFI (most feed efficient) and high RFI pigs (less feed efficient) at post-weaning [ 12 ] and during the growing period [ 3 , 7 ]. Moreover, the concentration of IGF-1 in blood plasma of juvenile post-weaned pigs was correlated with RFI measured during the growing period [ 17 ], suggesting that circulating molecules may even serve as early indicators for FE.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood is widely used in human medicine and veterinary elds as a relevant and easy sampling source of biological information, since it transports a large variety of molecules including genes, transcripts, proteins, metabolites and non-coding regulatory RNA from all over the body. Their dynamics re ects homeostatic regulation [1][2][3], physiological changes [4,5] and variations in immune capacity [6,7]. Circulating molecules also provide valuable insights into complex phenotypes such as obesity and diabetes [8,9], health status [10], sensitivity to heat stress [11] and nutrient e ciency for productive outputs [3,7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are huge expectations to nd predictive molecular biomarkers for incorporating FE in breeding programs or nutritional decision tools. So far, various studies have revealed differences in the whole blood transcriptome between low RFI (most feed e cient) and high RFI pigs (less feed e cient) at post-weaning [12] and during the growing period [3,7]. Moreover, the concentration of IGF-1 in blood plasma of juvenile post-weaned pigs was correlated with RFI measured during the growing period [17], which suggests that circulating molecules may even serve as early indicators for FE.…”
Section: Introductionmentioning
confidence: 99%